Impact of Peripartum Nutritional Supplementation on Thyroid Hormones, Metabolites and Reproductive Peridata in Jafarabadi Buffaloes - Vala, KB; Dhami, AJ; Kavani, FS; Bhanderi, BB; Parmar, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Forty advanced pregnant Jafarabadi buffaloes of 2-4 parity were divided into two equal groups, viz., control and treatment (n = 20 each).The animals of control group were maintained on routine farm feeding schedule and those under treatment group were subjected toadditional oral supplements daily with 50 g of chelated mineral mixture and 150 g of bypass fat along with concentrates for 6 weeksprepartum till 2 weeks postpartum, and then bypass fat was given @ 15 g/litre of milk produced till 60 days postpartum. All the buffaloeswere subjected to blood collection on day -45, -30, -7, 0, 7, 15, 30, 45 and 60 peripartum. Postpartum animals were followed at weeklyinterval by per rectal palpation and ultrasonographically for uterine involution, first postpartum estrus and conception. The overallmean blood glucose of prepartum period increased significantly (p
Keywords: Blood metabolites; Jafarabadi buffalo; Nutrient supplementation; , Postpartum fertilit; , Thyroid hormones profile; Transitional period.